Exploring the Role of Refugee Entrepreneurs in South Africa: A Quantitative Study on Networks, Bulk Buying, and Profitability - Awonke Geqeza; Anthony Kambi Masha (International Journal of Business, Economics, and Social Development, 2025)
This study explores the contribution of refugee entrepreneurship (RE) to South Africa's economy, a topic that remains under-researched despite the critical role these entrepreneurs play in job creation and employment. Employing a quantitative research approach, data were collected from 197 purposively selected participants through self-administered questionnaires. The data was analysed using SPSS and AMOS statistical software. The findings reveal that networks significantly contribute to business success by providing access to crucial resources, such as financing and market information. Refugee entrepreneurs leverage these, networks to overcome business challenges, receive financial support, and expand their entrepreneurial ventures. Additionally, bulk buying strategies reduce operational costs and enhance profitability. The study’s results also highlight the role of refugee businesses in filling gaps in underserved markets, as well as fostering collaboration with South African businesses, leading to the creation of jobs for local citizens. This research underscores the economic dynamism, job creation, and market diversification that refugee entrepreneurs contribute to South Africa's economy, emphasising their role as an essential driver of inclusive growth and economic stability in host countries.